Two-step absorption instead of two-photon absorption in 3D nanoprinting - Hahn, Vincent; Messer, Tobias; Bojanowski, N. Maximilian; Curticean, Ernest Ronald; Wacker, Irene; Schröder, Rasmus R.; Blasco, Eva; Wegener, Martin (Nature photonics, 2021)
The quadratic optical nonlinearity arising from two-photon absorption provides the crucial spatial concentration of optical excitation in three-dimensional (3D) laser nanoprinting, with widespread applications in technical and life sciences. Femtosecond lasers allow for obtaining efficient two-photon absorption but are accompanied by a number of issues, including higher-order processes, cost, reliability and size. Here we introduce two-step absorption replacing two-photon absorption as the primary optical excitation process. Under suitable conditions, two-step absorption shows the same quadratic optical nonlinearity as two-photon absorption. We present a photoresist system based on a photoinitiator supporting two-step absorption, a scavenger and a well-established triacrylate. We show that this system allows for printing state-of-the-art 3D nanostructures and beyond. In these experiments, we use ~100 μW optical power from an inexpensive, compact continuous-wave semiconductor laser diode emitting at 405 nm wavelength. Our work opens the door to drastic miniaturization and cost reduction of 3D laser nanoprinters.